Repairing annulus fibrosus fissures using methacrylated gellan gum combined with novel silk - Croft, Andreas F. (2023)
Intervertebral disc (IVD) herniation often causes severe pain and is frequently associated with the degeneration of the IVD. As the IVD degenerates, more fissures with increasing size appear within the outer region of the IVD, the annulus fibrosus (AF), favoring the initiation and progression of IVD herniation. For this reason, we propose an AF repair approach based on methacrylated gellan gum (GG-MA) and silk fibroin. Therefore, coccygeal bovine IVDs were injured using a biopsy puncher (â 2 mm) and then repaired with 2% GG-MA as a filler material and sealed with an embroidered silk yarn fabric. Then, the IVDs were cultured for 14 days either without any load, static loading, or complex dynamic loading. After 14 days of culture, no significant differences were found between the damaged and repaired IVDs, except for a significant decrease in the IVDsâ relative height under dynamic loading. Based on our findings combined with the current literature that focuses on ex vivo AF repair approaches, we conclude that it is likely that the repair approach did not fail but rather insufficient harm was done to the IVD.